Mapping Corporate Responsibility and Sustainable Supply Chains: an Exploratory Perspective - Carbone, Valentina; Moatti, Valerie; Vinzi, Vincenzo Esposito (Business strategy and the environment, 2012)
ABSTRACT Corporate responsibility (CR) in general, and sustainable supply chain management in particular, have been a growing concern for companies and researchers over the past decade. However, in scholarly work, sustainability has often been dealt with in a generic fashion or from an anecdotal point of view. Further, research works examining CR on the one hand and sustainable supply chains on the other have been conducted separately. We undertake the multiple factor analysis of a CR rating database (Innovest) which reports longitudinal scores for both the social and environmental performance of 1198 companies in different countries and distinct industries, to demonstrate a strong relationship between CR and a sustainable supply chain. Our findings from exploratory analysis also illustrate the role of country of origin and industry in shaping CR behaviour, highlighting isomorphic as well as allomorphic trends for CR trough time. Copyright © 2012 John Wiley & Sons, Ltd and ERP Environment.